Combined action observation and motor imagery practice for upper limb recovery following stroke: a systematic review and meta-analysis - Lin, Dan; Eaves, Daniel Lloyd; Franklin, John Derek; Robinson, Jonathan Richard; Binks, Jack Aaron; Emerson, Jonathan Reyes (Frontiers in Neurology, 2025)
IntroductionOptimal upper limb recovery requires high-dose physiotherapy; however, this essential component of rehabilitation is under-delivered. Mental practice represents an accessible and cost-effective adjunct to conventional therapy. We therefore evaluated the efficacy of an enhanced mental practice treatment (combined action observation and motor imagery, AO + MI) for promoting upper limb recovery post stroke.MethodsSearching 10 databases, we identified 18 eligible studies (N = 336), comprising nine randomized controlled trials (RCTs) and nine non-randomized controlled trials (non-RCTs). RCTs were meta-analyzed using upper limb function outcomes (Fugl-Meyer Assessment for upper extremity, FMA-UE; Action Research Arm Test, ARAT). Non-RCTs (not eligible for meta-analysis) were narratively synthesized using upper limb and neuroimaging outcomes.ResultsSeven RCTs reported FMA-UE scores (n = 189), where the standardized mean difference (SMD) for AO + MI treatments was moderate (SMD = 0.58, 95%CI: 0.13–1.04, p = 0.02). Two additional RCTs reported ARAT scores. Meta-analyzing the combined FMA-UE and ARAT scores (n = 239) revealed SMD = 0.70 (95%CI: 0.32–1.09, p = 0.003). No significant correlations existed between the pooled effect size and several moderators (age, time since stroke, intervention duration, control condition, outcome measure and AO + MI arrangement), indicating consistent AO + MI practice effects. Overall, AO + MI significantly improved upper limb function across all nine RCTs, and all nine narratively synthesized studies, including neuroimaging outcomes. Limitations included inconsistent terminology, intervention design, clarity of reporting, and modality.DiscussionAO + MI practice can promote upper limb recovery following stroke. AO + MI can therefore be used as a bridge between AO therapy (requiring little effort in early recovery), and the more cognitively demanding MI. Researchers must adopt standardized reporting protocols to further establish AO + MI practice efficacy.Systematic review registrationThe review was registered with PROSPERO under the registration number CRD42023418370. The registration is publicly accessible at the following URL: https://www.crd.york.ac.uk/PROSPERO/view/CRD42023418370.